PENGARUH KUALITAS PELAYANAN BPJS KESEHATAN TERHADAP KEPUASAN PENGGUNA PERSPEKTIF DOKTER RUMAH SAKIT HERMINA BOGOR - Putri, Baby Silvia; Kartika, Lindawati (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
The study aimed to analyze the perceptions of the doctors of Hermina Hospital Bogor on BPJS health service quality and satisfaction level of the national health insurance program and to analyze the effects of service quality on the doctors’ satisfaction. Questionnaires were utilized to obtain the primary data, while literature reviews were conducted to obtain the secondary data. The data were analyzed by using descriptive analysis and multiple regression analysis. The results of this research, in reference to the descriptive analysis of the perceptions of the doctors in Hermina Hospital Bogor on satisfaction and quality service of the National Health Insurance program, indicated that the program is considered unsuitable in its implementation. The results of multiple regression showed that the variables of BPJS service quality have influences on the satisfaction of the doctors of Hermina Hospital Bogor. Keywords: health service quality, satisfaction, hospital